Factores de riesgo de mortalidad en adulto mayor sometido a cirugía por abdomen agudo quirúrgico - Miñano Quiroz, Marco Antonio (2018)
Determine whether the operative time and the number of comorbidities are risk factors for mortality in older patien expose to urgency abdominal surgery in Belen Trujillo Hospital during the years 2009– 2014. Material and method: Study analytic, observational, retrospective, cases and controls. The population were integrated by 204 older patiens of 60 years expose to urgency abdominal surgery, established as inclusión and exclusión criteria and divided into two groups: 68 cases and 134 controls. Results: The estadistical analysis about the variables in study were to mortality: operative time >=2h (OR: OR= 1,65 , p=0,0923) and number of comorbidities >2 (OR: 2,38 y p=0,004). Conclusions: The number of comorbidities greater than 2 was a risk factor for mortality in the elderly subject to surgery for acute surgical abdomen, but not the operative time greater than or equal to 2 hours, which was not significant